2013
DOI: 10.1152/ajpheart.00235.2012
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal nitric oxide synthase expression is lower in areas of the nucleus tractus solitarius excited by skeletal muscle reflexes in hypertensive rats

Abstract: Murphy MN, Mizuno M, Downey RM, Squiers JJ, Squiers KE, Smith SA. Neuronal nitric oxide synthase expression is lower in areas of the nucleus tractus solitarius excited by skeletal muscle reflexes in hypertensive rats. Am J Physiol Heart Circ Physiol 304: H1547-H1557, 2013. First published April 5, 2013; doi:10.1152/ajpheart.00235.2012.-The functions of the skeletal muscle exercise pressor reflex (EPR) and its mechanically sensitive component are augmented in hypertension producing exaggerated increases in bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 41 publications
(60 reference statements)
7
24
0
Order By: Relevance
“…Heart weight-tobody weight ratio as well as heart weight-to-tibial length ratio were significantly greater in SHR than WKY as previously reported (42,43,47,60). Further, exercise training significantly increased these ratios in both WKY and SHR.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Heart weight-tobody weight ratio as well as heart weight-to-tibial length ratio were significantly greater in SHR than WKY as previously reported (42,43,47,60). Further, exercise training significantly increased these ratios in both WKY and SHR.…”
Section: Resultssupporting
confidence: 85%
“…Consistent with our previous studies, EPR function was abnormally heightened in untrained SHR compared with WKY (26,42,43,47,60). This characteristic EPR overactivity has been shown to manifest not only in SHR but also in other models of the disease such as prenatally programmed hypertension (41,44) and angiotensin II-induced hypertension (24).…”
Section: Exercise Training Attenuates Epr Function In Shrsupporting
confidence: 90%
See 1 more Smart Citation
“…A third possibility is that enhanced GBR expression in the NTS of SHR may be caused by other neural modulators, such as nitric oxide (NO) or reactive oxygen species (ROS). It has been reported that NO production in the NTS of SHR is reduced as compared with WKY rats (16), and enhanced NO production in this brain area by overexpression of eNOS lowers blood pressure in SHR (17). On the other hand, ROS generation in the NTS is increased in SHR.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that centrally-derived nitric oxide inhibits sympathetic outflow 109,110) . Using immunohistochemical and western blotting techniques, we showed that the expression of at least one isoform of nitric oxide synthase protein (i.e., neural nitric oxide synthase) is lowered throughout a large portion of the NTS in hypertensive compared to normotensive rats 111) . From such investigation, we further demonstrated that reducing the endogenous production of nitric oxide within the NTS generates overactive muscle mechanoreflex activity in normotensive rats similar to that exhibited in hypertensive animals 112) .…”
Section: Central Mechanisms Of Exercise Pressor Reflex Dysfunction Inmentioning
confidence: 96%